Marked gender inequity in the invited speakers at the European College of Veterinary Surgeons annual scientific congress 2012–2022 - Pratschke, Kathryn; Bristow, Poppy; Paczesna, Alina; Parakh, Ishita; MacKay, Jill R. D.; Mackay, Fiona; Blacklock, Kelly (PloS one, 2025)
The objective of this retrospective study was to explore gendered equity for invited speakers at the European College of Veterinary Surgery (ECVS) Annual Scientific Meeting between 2012–2022 when compared to speciality demographics for ECVS membership. Our sample populations included the European College of Veterinary Surgeons (ECVS) Diplomate membership, and all invited speakers at their Annual Scientific Meetings between 2012–2022. Data was extracted from Meeting Programs including year, speaker name, session type, and frequency of invitation. Authors were assigned a binary gender using a web-based algorithm to determine gender by a first name. The number and gender of new Diplomates each year between 1993–2023 was obtained from the ECVS Office and used as a comparison group to assess proportional representation amongst invited speakers. We found that women comprised 27% (249/924) of ECVS Diplomates in 2012 and 33.82% (312/924) in 2022. In this decade, there were 913 invited lectures delivered at ECVS Annual Scientific Meetings, 21% (188/913) were delivered by women. Women were particularly under-represented for higher prestige lectures including State of the Art (0%), Pre-Congress wet labs (0%) and Pre-Congress expert-led sessions (15.8%, 15/95). In conclusion, the proportion of invited speakers that were women at ECVS Scientific Meetings between 2012–2022 was 21%, despite women comprising >25% of ECVS Diplomate membership since 2012. Higher prestige sessions were heavily biased towards speakers being men. We suggest proactive commitment is needed to achieve gender equity in speaker invitations across all session types at ECVS Annual Scientific Meetings.